INVESTIGATION OF Ni-CONTAINING CATALYSTS FOR THE PURIFICATION OF EXHAUST GASES - Zheksenbaeva Z.T.; Sarsenova R.O.; Tungatarova S.A.; Baizhumanova T.S.; Zhevnitskiy S.I.; Romanenko S.V. (Academic Scientific Journal of Chemistry, 2020)
Results of the development of multicomponent oxide catalysts for the purification of exhaust gases based on Ni, Cu, and Cr supported on 2% Ce/θ-Al2O3 by varying the concentration of the active phase of catalyst are presented in paper. It was found that the highest degree of toluene conversion (up to 98.8 %) is observed on the three-component Ni-Cu-Cr/2% Ce/θ-Al2O3 catalyst with optimal metal ratio Ni : Cu : Cr = 1.0 : 3.0 : 0.1 at GHSV = 5Ч103 h-1 and a temperature of 723 - 773 K. The presence of CeO2 crystals, X-ray amorphous clusters (d = 20 – 100 Е) of variable valence metal oxides NiO and CuO as well as solid metal solutions CuO (NiO) and aluminates was detected on the surface of optimum catalyst calcined at 873 K using XRD and transition electron microscopy methods. Preparation of polyoxide supported catalysts as well as study the influence of catalyst composition and modified additives on deep oxidation of toluene - a major component of toxic organic gaseous industry emissions, is the goal of research.